SYNTHESIS OF A NEW ADSORBENT BASED ON THE MILD DEALUMINATED BINDER FREE GRANULAR Y ZEOLITE - Ahmed, Kanaan R.; Mohammed, Dlzhar S.; Ali, Farhad M. (Science Journal of University of Zakho, 2023)
This study investigates, for the first time, the effects of dealumination of binder-free NaY type zeolite on the adsorption properties and porous structure characteristics. In this study, BF-Y zeolite was hydrothermally synthesized from kaolin and powder NaY. BF-Y was then treated with acid to increase Si/Al ratio. X-ray Diffraction (XRED), Thermal Gravimetric Analysis (TGA), Scanning Electron Microscope (SEM), and Energy Dispersive X-Ray (EDX) have been performed for the characterization. The modified zeolite granules MBF-Y were used as an adsorbent for the removal of methylene blue MB dye from water. The influence of initial MB concentration, contact time, temperature, and adsorbent dosage on adsorption capacity and dye removal percentage on MBF-Y was investigated. The maximum dye removal was attained at a concentration of (8 * 10-6 M) which was more than 93%, and an equilibrium contact time of 60 minutes. Well-known adsorption isotherms (Langmuir, Fruendlich, and Tempkin) were used to study the adsorption mechanism of MB onto MBF-Y.